The Scarlatti inheritance - Ludlum, Robert (Garden City, New York : Doubleday, 1971)
Say No to Murder has 299 ratings and 15 reviews. Mary JL said: The Jenny Cain Mysteries, set in New England, have a strong heroine
Keywords: Fiction -- Action